2022
DOI: 10.1002/smll.202204941
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Immune Cell, AI‐cell, a New Tool to Predict Interferon Production by Peripheral Blood Monocytes in Response to Nucleic Acid Nanoparticles

Abstract: Nucleic acid nanoparticles, or NANPs, rationally designed to communicate with the human immune system, can offer innovative therapeutic strategies to overcome the limitations of traditional nucleic acid therapies. Each set of NANPs is unique in their architectural parameters and physicochemical properties, which together with the type of delivery vehicles determine the kind and the magnitude of their immune response. Currently, there are no predictive tools that would reliably guide the design of NANPs to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…In our study, we conduct a series of experiments to assess whether DNA triangles with various ssT regions would elicit an immune response or prove to be toxic to human cells. We utilize three different reporter cell lines (HEK-Blue hTLR7, HEK-Blue hTLR9, and HEK-Lucia RIG-I) engineered to turn up the activation of specific pathways related to the detection of exogenous nucleic acids. While TLR9 is a well-known key receptor for the recognition of DNA, TLR7 primarily recognizes ssRNAs. However, it has been reported that TLR7 also has the ability to respond to deoxyguanosine, independent of RNA. , Furthermore, recent studies have indicated the possible recognition of DNA nanoparticles by TLR7 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we conduct a series of experiments to assess whether DNA triangles with various ssT regions would elicit an immune response or prove to be toxic to human cells. We utilize three different reporter cell lines (HEK-Blue hTLR7, HEK-Blue hTLR9, and HEK-Lucia RIG-I) engineered to turn up the activation of specific pathways related to the detection of exogenous nucleic acids. While TLR9 is a well-known key receptor for the recognition of DNA, TLR7 primarily recognizes ssRNAs. However, it has been reported that TLR7 also has the ability to respond to deoxyguanosine, independent of RNA. , Furthermore, recent studies have indicated the possible recognition of DNA nanoparticles by TLR7 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, fibrous materials offer a large surface area, allowing the delivery of a more significant number of functional moieties than a spherical nanocarrier may offer. Moreover, a nonspherical shape has been suggested to improve the vascular transport of nanomaterials and therapeutic cargo delivery into the interstitial space. , To leverage these benefits of fibrous shape while avoiding undesirable inflammatory responses, researchers turned their attention to “soft” and biodegradable materials such as those made of natural RNA and DNA biopolymers. The field of nucleic acid nanoparticles (NANPs) is fast growing and has already demonstrated numerous beneficial, safe, and environmentally friendly applications ranging from therapeutic indications as nanomedicines to the use as structural components of light-emitting diodes, functional photonic devices, and biosensors. …”
mentioning
confidence: 99%
“…A series of earlier studies demonstrated that after the complexation with a carrier, NANPs can be specifically delivered to and internalized by the immune cells such as blood monocytes and dendritic cells. Upon such targeted intracellular delivery, NANPs differentially stimulate cytokine production based on their physicochemical properties and architectural parameters. , Specifically, NANPs delivered by lipofectamine differentially induce cytokines based on NANPs’ composition (i.e., RNA nanoparticles are more potent cytokine inducers than their DNA counterparts), shape (i.e., globular NANPs show greater immunostimulation than planar and fibrous NANPs while planar NANPs have superior responses when compared to fibrous), size (i.e., larger NANPs are more proinflammatory than their smaller analogs), and functionalization (i.e., functionalized NANPs are more immunostimulatory compared to their nonfunctionalized counterparts). ,, These responses depend on endosomal toll-like receptors, particularly TLR7, and culminate with the production of type I and type III interferons …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the reported technology holds promise for the future of TNBC management and offers potential for expanding therapeutic applications of nucleic acid nanotechnology, it is important to recognize that some additional studies may be necessary to address certain potential limitations. Depending on their composition and architectural parameters, RNA nanoparticles are known to activate various immune responses and thereby may cause adverse reactions 7 , 8 that may preclude further clinical implementations. Detailed studies using well-established experimental protocols 9 aiming to elucidate the immunorecognition of newly developed nucleic acid nanoparticles will provide some additional insights to relevant immunological responses that may occur upon the systemic administration of 3WJ- 9-apt-anti-miR21 nanoparticles or any other potential therapeutic agents.…”
mentioning
confidence: 99%